Physiological, Diurnal and Stress-Related Variability of Cadmium-Metallothionein Gene Expression in Land Snails - Pedrini-Martha, Veronika (PLoS One, 2016)
The terrestrial Roman snail Helix pomatia has successfully adapted to strongly fluctuating conditions in its natural soil habitat. Part of the snail’s stress defense strategy is its ability to express Metallothioneins (MTs). These are multifunctional, cysteine-rich proteins that bind and inactivate transition metal ions (Cd(2+), Zn(2+), Cu(+)) with high affinity. In Helix pomatia a Cadmium (Cd)-selective, inducible Metallothionein Isoform (CdMT) is mainly involved in detoxification of this harmful metal. In addition, the snail CdMT has been shown to also respond to certain physiological stressors. The aim of the present study was to investigate the physiological and diurnal variability of CdMT gene expression in snails exposed to Cd and non-metallic stressors such as desiccation and oxygen depletion. CdMT gene expression was upregulated by Cd exposure and desiccation, whereas no significant impact on the expression of CdMT was measured due to oxygen depletion. Overall, Cd was clearly more effective as an inducer of the CdMT gene expression compared to the applied non-metallic stressors. In unexposed snails, diurnal rhythmicity of CdMT gene expression was observed with higher mRNA concentrations at night compared to daytime. This rhythmicity was severely disrupted in Cd-exposed snails which exhibited highest CdMT gene transcription rates in the morning. Apart from diurnal rhythmicity, feeding activity also had a strong impact on CdMT gene expression. Although underlying mechanisms are not completely understood, it is clear that factors increasing MT expression variability have to be considered when using MT mRNA quantification as a biomarker for environmental stressors.